Epidemiology of vector-borne diseases - Harrington, Laura C. (Henry Stewart Talks, 2010)
Introduction to the field of epidemiology, Determinants of disease, Epidemiological measures, Field based epidemiology of vector-borne diseases
Reviewed at 2020/06/12, Archived at 2023/01/31